PELUANG DAN TANTANGAN SUMBER DAYA MANUSIA DI ERA DIGITAL : SEBUAH TINJAUAN - Lola Malihah; Sarmila Normala (LP2M Universitas Bina Bangsa, 2024)
The development of science and technology has brought many changes to all aspects of life including the human resource management sector. Not a few jobs that were originally carried out by humans have now begun to be replaced by technology which has an impact on the increasingly difficult to obtain job opportunities, thus also having an impact on the number of unemployment. Only a skilled and qualified workforce will be able to survive the increasingly fierce job competition. This paper is a literature review that aims to examine the opportunities and challenges of human resources in the digital era. From several references that became references, data were obtained on several human resource challenges in the digtal era, namely changes in work culture, mobility management and flexibility as well as skill demands for the use of technology. While the opportunities are in the form of the use of big data analytics, employee development and increased employee involvement in the organization. Technology and digitalization are inevitable, but qualified and competent human resources will be able to survive and keep pace with technological sophistication. With policies and regulations, of course, technology will support human resources in doing all work